IMPLEMENTASI PRINSIP TATA PEMERINTAHAN YANG BAIK DALAM PENGAWASAN PENDAFTARAN HAK ATAS TANAH - Rommy Hardyansah (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2019)
The Opening of the 1945 Constitution of the Republic of Indonesia Paragraph IV is the NRI's State of Interest. In order to realize the mandate of the constitution, a system of state and government administrationis needed based on the principle of good governance by involving various parties, both the state administration and the people. Land Registration regulated in Government Regulation No. 24 of 1997. Land registration has various problems including double certificates; fake certificate; conversion of rights that arelegally flawed. The Saber Pungli Team did arrest employees in the office of Malang City National Land Agency. These problems indicate that BPN as a state institution does not provide public services in accordance with the principles of Good governance..Keywords: Good Governance, Land Registration, Supervision, Implementation of Good Governance.